ANALYSIS OF INFLUENCE OF PHYSICAL NEEDS MOTIVATION, SECURITY, SOCIAL, SELF-ESTEEM, AND SELF-ACTUALIZATION ON EMPLOYEE JOB SATISFACTION AT PT. SARI TEMBAKAU HARUM KENDAL - Suwandi, Difa Anggraini; Poerbo, Suryadi; Devie, Erika (Politeknik Negeri Semarang, 2019)
The purpose of this research was find out the influence physical need motivation, security, social, self-esteem, and self-actualization on employees jobs saticfaction, and how much was that influenced. The method of analysis in this research used validity test, reliability test, multiple linear regression test, t test, f test, and the coefficient of determination. The result obtained from testing of 5 variable hypothesis t-test > t-table 1.(3,477>1,661), 2.(2,496>1,661), 3.(3,370>1,661), 4.(6,266>1,661), 5.(5,103>1,661) so we could conclude that Ha was accepted and Ho was rejected. The results obtained from testing of f test, show that f test > f table (240,820>2,31) so we could conclude that h1 was accepted. From the results show the value of the coefficient of determination was 0,924, indicating that the motivation to work had the effect of 92,4% on job satisfaction and the rest was influenced by other factors which were not examined in this study